2017
DOI: 10.5530/ijper.51.3s.68
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Oil Compositions of Origanum majorana L. Cultivated in Konya and Collected from Mersin-Turkey

Abstract: Purpose: In this study, essential oil (EO) compositions of the dried and fresh aerial parts of Origanum majorana cultivated in the research field and collected from f from Mersin was investigated. Material and Methods: EO was distilled by using Clevenger type apparatus for 3 h and the chemical compositions were detected in GC-MS. While, the oil yields of the the collected marjoram was determined to be 2,5 ml both in dried and fresh aerial parts, the yields of the cultivated plants for fresh and dried parts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
0
5
0
1
Order By: Relevance
“…Commonly used for seasoning of salads, soups, dressings and for herbal teas . 14 In the present study, Origanum majorana showed anthelmintic activity against the Earthworm model. Studies have reported effective antibacterial, antiviral and nematocidal activity of theOriganum plant .…”
Section: Discussionmentioning
confidence: 47%
“…Commonly used for seasoning of salads, soups, dressings and for herbal teas . 14 In the present study, Origanum majorana showed anthelmintic activity against the Earthworm model. Studies have reported effective antibacterial, antiviral and nematocidal activity of theOriganum plant .…”
Section: Discussionmentioning
confidence: 47%
“…Origanum L., which belongs to the Lamiaceae family, is an annual, perennial, or shrubby plant [1]. There are 57 species of oregano that grow naturally in the world [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most important medicinal and aromatic plants and is considered as an important economic agricultural export crop [1,2]. Marjoram, a herb, and its essential oils (EOs), are used in the food industry in condiments and as food preservatives, and it is also used for its medicinal properties as a stomachic, carminative, expectorant and antispasmodic agent [3][4][5]. Marjoram EO has been studied for its antibacterial, antifungal and antiviral activities, as an insecticide and in pharmaceutical and industrial products [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%